Construction and analysis of a survival-associated competing endogenous RNA network in breast cancer - Chen, Gang; Li, Yalun; Cao, Jianqiao; Dai, Yuanping; Cong, Yizi; Qiao, Guangdong (Frontiers in Surgery, 2023)
Background: Increasing studies have shown that noncoding RNAs are closely related to the progression and metastasis of cancer by participating in competing endogenous RNA (ceRNA) networks. However, survival-associated ceRNAs in breast cancer (BC) are still unknown. Methods: The Gene Expression Omnibus database and The Cancer Genome Atlas BRCA_dataset, and differentially expressed (DE) RNAs were identified. Furthermore, circRNA-miRNA interactions were predicted based on CircInteractome, and miRNA-mRNA interactions were predicted based on TargetScan, miRDB and miRTarBase. Therefore, survival-associated ceRNA networks were constructed based on the predicted circRNA-miRNA and miRNA-mRNA pairs. Finally, the mechanism of the miRNA-mRNA pairs was determined. GO and KEGG analyses of survival-related mRNAs were performed using the Hypergeometric Distribution formula in R software. The prognosis of hub genes was verified using gene set enrichment analysis. Results: Based on the top ten initial candidate DE-circRNAs, we obtained a total of 162 DE-miRNAs and a total of 34 DE-miRNAs associated with significant overall survival. Then, the miRNA target genes were identified using online tools and verified using the TCGA database. Overall, 46 survival-associated DE-mRNAs were obtained. GO and KEGG pathway enrichment analysis implied that up-regulated survival-related DE-mRNAs were mostly enriched in the ‘regulation of cell cycle’, ‘chromatin’. Down-regulated survival-related DE-mRNAs were mostly enriched in ‘‘negative regulation of neurotrophin TRK receptor signaling pathway’, ‘interleukin-6 receptor complex’ pathways. Finally, the survival-associated circRNA-miRNA-mRNA ceRNA network was constructed using 34 miRNAs, 46 mRNAs, and 10 circRNAs. Based on the PPI network, 2 ceRNA axes were identified and could be considered biomarkers for BC. GSEA revealed that the hub genes correlated with ‘VANTVEER_BREAST_CANCER_POOR_PROGNOSIS’, and the hub gens were verified using BC patients tissues. Conclusions: In this study we constructed a circRNA-mediated ceRNA network related to BC. This network provides new insight into discovering potential biomarkers for the diagnosis and treatment of BC.